2017
DOI: 10.1016/j.neuroimage.2016.04.049
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Epileptic Patient: Individualized whole-brain models of epilepsy spread

Abstract: Individual variability has clear effects upon the outcome of therapies and treatment approaches. The customization of healthcare options to the individual patient should accordingly improve treatment results. We propose a novel approach to brain interventions based on personalized brain network models derived from non-invasive structural data of individual patients. Along the example of a patient with bitemporal epilepsy, we show step by step how to develop a Virtual Epileptic Patient (VEP) brain model and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
402
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(411 citation statements)
references
References 59 publications
7
402
0
2
Order By: Relevance
“…Results showed that individual optimization of the modeling parameters significantly increased the prediction accuracy of individual functional connectivity. However, whether model parameters were tuned on the individual SC matrices or on the average SC matrix across all control subjects did not yield a significant difference, corroborating findings in previous research (e.g., Jirsa et al, 2017). Future computational modeling studies could use finer and more elaborated parcellation schemes, for example based on multimodal data (Glasser et al, 2016), to investigate whether individual traits can be captured through tractography that have relevance for the prediction of individual functional connectivity.…”
Section: Discussionsupporting
confidence: 86%
“…Results showed that individual optimization of the modeling parameters significantly increased the prediction accuracy of individual functional connectivity. However, whether model parameters were tuned on the individual SC matrices or on the average SC matrix across all control subjects did not yield a significant difference, corroborating findings in previous research (e.g., Jirsa et al, 2017). Future computational modeling studies could use finer and more elaborated parcellation schemes, for example based on multimodal data (Glasser et al, 2016), to investigate whether individual traits can be captured through tractography that have relevance for the prediction of individual functional connectivity.…”
Section: Discussionsupporting
confidence: 86%
“…While different models of effective connectivity have been proposed (for a comprehensive summary, see Valdes-Sosa et al, 2011), to our knowledge, none has so far enabled estimates of connection-specific strengths for networks derived from typical whole-brain parcellation schemes with more than 100 nodes (Glasser et al, 2016;Tzourio-Mazoyer et al, 2002). For instance, biophysical network models (BNMs) combine mean-field models of local neuronal dynamics with anatomical data on long-range connections, capturing many structural and physiological details of whole-brain networks (Deco et al, 2013a;Jirsa et al, 2016). However, the complexity of these models has made parameter estimation computationally extremely challenging.…”
mentioning
confidence: 99%
“…A comprehensive presur-gical evaluation is necessary to pinpoint the epileptogenic zone along with the identification of the risks of postoperative neurologic morbidity. Based on structural anomalies as identified by MRI and the assessment of functional data such as EEG, estimation of TVB parameters (epileptogenicity, anomalies) are set in the network model to predict the propagation pattern of seizures in order to explore brain intervention strategies [41]. …”
Section: The Virtual Brain-derived Models Are Sensitive To Disruptionmentioning
confidence: 99%
“…The network model is composed of two neuronal populations, characterized by fast excitatory bursting neurons and regular spiking inhibitory neurons, embedded in a common extracellular environment represented by a slow variable. By systematically analyzing the parameter landscape via the simulation, it is possible to reproduce typical sequences of neural activity observed during status epilepticus [41,42]. …”
Section: The Virtual Brain-derived Models Are Sensitive To Disruptionmentioning
confidence: 99%
See 1 more Smart Citation